Integrasi Content Marketing Model AIDA dan Customer engagement dalam meningkatkan Brand Awareness serta Implikasinya terhadap Keputusan Pembelian Produk Skintific - Dewi, Ni Kadek Lia Setia; Adriati, I Gst. Ayu Wirati; P, Komang Widhya Sedana Putra; Widiantari, Komang Sri (Masyarakat Ekonomi Syariah Bogor, 2025)
The development of the digital era has fundamentally transformed the global industrial landscape, especially in the beauty and skincare industry. In Indonesia, a similar phenomenon has occurred significantly. The Central Statistics Agency (2022) noted that the cosmetics industry, including skincare, experienced a growth of 9.61% in 2022. Skintific was able to dominate the market in 2024, successfully breaking through sales figures of IDR 70 billion with its strong digital marketing strategy. This study aims to empirically prove the integration of the AIDA content marketing model and customer engagement in increasing brand awareness and its implications for purchasing decisions for Skintific products. This study uses quantitative analysis techniques. The research population consists of Gen Z buyers of Skintific products in Denpasar City, using non-probability sampling with a purposive sampling technique and a Partial Least Squares - Structural Equation Modeling approach. Based on this sampling technique, 140 Gen Z buyers of skintific products in Denpasar City were selected as samples. The type of data used is primary data using questionnaires and utilizing mediation regression analysis to determine the influence between independent variables, dependent variables, and mediating variables. The results of this study show that the AIDA content marketing model and customer engagement have a significant positive effect on brand awareness. The AIDA content marketing model, customer engagement, and brand awareness have a significant positive effect on purchasing decisions, and brand awareness can strengthen the influence of the AIDA content marketing model and customer engagement on purchasing decisions.